Cat scratch disease in a 23-year-old male-Case report - Radeyah Waseem; Muskan Seher; Sohiba Ghazal; Hussain Haider Shah; Ume Habiba (Frontiers Media S.A., 2023)
Cat-scratch disease (CSD) is an infectious disease that usually presents with fever, headache, loss of appetite, weight loss, tender lymphadenopathy, and other symptoms. CSD is also the most common cause of infectious lymphadenitis in children, adolescents, and young adults. This contagious disease most often results from a scratch or bite of a cat. The course of this disease depends on the patient's immune status. CSD sometimes presents as a systemic disease and leads to various disease entities. In this study, we describe the case of a 23-year-old man exhibiting fever, generalized weakness, and neck swelling. The patient was unconscious when presented to the Emergency Department. He was given at least 3-4 liters IV bolus of 0.9% normal saline, but it failed to raise the blood pressure. He was then given an inotropic drug (noradrenaline) for low blood pressure and antibiotics (azithromycin) for fever. Venereal disease research laboratory (VDRL) and human immunodeficiency virus (HIV) serology came out negative. Histopathology ruled out tuberculosis and malignancy and confirmed necrotizing/suppurative granulomatous inflammation. These features favor the diagnosis of CSD.